Analisis Yuridis Larangan Perkawinan Semarga dalam Adat Karo terhadap Hukum Perkawinan - Almanda Aretta Mayra br Sinuraya; Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to determine the knowledge of the prohibition of marriage between clans in Karo customary law and to determine the suitability of this prohibition with national marriage law in Indonesia. The type of research uses normative legal research which is descriptive-prescriptive in nature. The type of approach used is the approach of legislation and customary law provisions. The technique of collecting legal materials in this study is the legal material analysis technique. The data analysis used is qualitative analysis. Based on this study it can be seen that (1) The Regulation of the Prohibition of Marriage Between Clans in Karo Customary Law is based on a patrilineal kinship system that places merga as the main identity, so that marriage between clans is considered to violate customary norms and is subject to social and customary sanctions. (2) The suitability of the prohibition on marriages based on the same surname in Karo Custom with National Marriage Law in Indonesia, shows that normatively there is no explicit prohibition in positive law as long as it does not violate the provisions on blood relations as regulated in statutory regulations, however national law still provides space for recognition of customary law, so that harmonization is needed to guarantee legal certainty and protection of the cultural values of indigenous communities.